Asuhan Keperawatan Ibu Hamil Trimester III pada Ny.M dengan Nyeri Punggung Melalui Intervensi Latihan Relaksasi Otot Progresif di Desa Sungai Batang Ilir Kecematan Martapura Barat - Bunga Indryan Noor Rindu Lestari; Devi Rahmayanti (Nerspedia, 2023)
Background: Pregnancy is a natural and physiological process. One of the health problems that often occurs in the third trimester of pregnancy is back pain. Back pain in the third trimester of pregnancy can arise due to the enlargement of the uterus so that the body posture changes, this can interfere with activities if not given treatment. Discomfort due to back pain is felt from mild to painful pain. Objective: This nursing care is to provide an overview of the effect of progressive muscle relaxation exercise interventions on pregnant women in the third trimester with back pain problems.